Clinical and epidemiological features of oral cancer in a medical school teaching hospital from 1994 to 2002: increasing incidence in women, predominance of advanced local disease, and low incidence of neck metastases Características clínicas e epidemiológicas do câncer da boca em hospital-escola de 1994 a 2002: aumento da incidência em mulheres, predomínio de doença local avançada e baixa incidência de metástases regionais - Marcelo D. Durazzo; Carlos Eugenio Nabuco de Araujo; José de Souza Brandão Neto; André de Souza Potenza; Pedro Costa; Flávio Takeda; Cristina Bianchi; Marcos R. Tavares; Gilberto de Britto e Silva Filho; Alberto R. Ferraz (Clinics, 2005)
PURPOSE: Description of clinical and epidemiological characteristics of patients who underwent surgery for oral cancer in a Medical School Teaching Hospital, and determination of differences with respect to other institutions and/or periods of time. METHOD: The charts of patients undergoing surgery for oral cancer from 1994 to 2002 were reviewed. Data were collected in a spreadsheet in order to analyze clinical and epidemiological features.. RESULTS: A total of 374 patients having undergone 406 operations was identified. Their ages varied from 14 to 94 years (mean = 57.4 years), with 255 men (68.2%), and 295 out 366 Caucasian (80.6%). A majority had tumors of the tongue and/or floor of mouth (55.6%), while 20.3% had lip cancer. Squamous cell carcinoma was found in 90.3%, and glandular carcinoma in 4%. T4 tumors in 39.6%, Tis or T1 lesions in 15.2% of all patients. Nearly 62% had no regional metastases, and the relative incidence in young patients (40 years or younger) reached 8.6%. CONCLUSION: In spite of the predominance of locally advanced tumors, a majority of patients had no neck metastases. The 31.8% incidence in females indicates an increasing incidence of oral cavity cancer among women when compared to previous periods at the same institution. OBJETIVO: Caracterizar epidemiológica e clinicamente a população atendida por câncer de boca em hospital-escola de atenção terciária e quaternária e verificar variações em relação a outras casuísticas e períodos. MÉTODO: Procedeu-se à revisão dos prontuários dos operados por câncer oral de 1994 a 2002. As características clínicas e epidemiológicas foram colocadas em planilhas e analisadas. RESULTADOS: Foram identificados 374 portadores de câncer da boca que foram submetidos a 406 operações. A idade dos doentes variou de 14 a 94 anos (média = 57,4 anos). Duzentos e cinqüenta e cinco eram do gênero masculino (68,2%). Duzentos e noventa e cinco entre 366 doentes eram caucasianos (80,6%). A maioria era portadora de tumores da língua e/ou do soalho da boca (194 entre 349 doentes; 55,6%), e 71 (20,3%) tinham tumores dos lábios. O carcinoma epidermóide foi encontrado em 90,3% e carcinomas glandulares em 4%. Os tumores T4 estavam presentes em 39,6% dos doentes; 15,2% tinham lesões Tis ou T1. Quase 62% dos pacientes não tinham metástases cervicais. A incidência relativa em jovens (com até 40 anos de idade) atingiu 8,6%. CONCLUSÃO: Apesar dos achados freqüentemente referidos na literatura terem se confirmado (como o predomínio de lesões avançadas localmente), a maioria dos doentes não apresentava metástases cervicais. Acima do observado em outras casuísticas, os 31,8% de mulheres na presente casuística indica a preocupante e crescente incidência no gênero feminino.